Factors affecting the simple febrile seizures in COVID-19 children: a case–control study from China - Wu, Haohao; Du, Kang; Liang, Xi; Fan, Huijuan; Ba, Ruiqiong; Yang, Junsu; Wang, Yue (Frontiers in Neurology, 2023)
The over-age phenomenon of children SFS was found during the epidemic in COVID-19, but there was no clear explanation, especially in China. This study aims to analyze the clinical and auxiliary examination features of simple febrile seizures (SFS) in children infected with novel coronavirus disease 2019 . Methods: Seventy-eight patients with SFS in the Department of Pediatric and Neurology of Qujing First People's Hospital were enrolled and divided into COVID-19 positive group (case group) and COVID-19 negative group (control group). The clinical characteristics, accessory examinations, and risk factors were analyzed. Results: There were significant differences in age stratification between the two groups. The proportion of children aged over 5 years old in the case group (47.4%) was higher than that of the control group (5%) (p<0.0001). In terms of gender distribution, the proportion of males in the case group was higher than that in the control group (71.1% v.s. 50%), but the difference was not statistically significant (p=0.0678). For blood cell analysis, the values of white blood cells (WBC), lymphocytes (LY) and monocytes (MN) in the case group were significant lower than those in the control group (p<0.01). Serum electrolyte analysis showed the greatest difference in blood sodium. The incidence of hyponatremia in the case group was higher than that in the control group (36.8% v.s. 17.5%), but the difference did not reach the statistical significance (p=0.0745). Multivariate Logitstic regression analysis showed that the FS history was a non-independent risk factor for SFS (OR=0.115, p=0.009), and age was an independent risk factor for SFS in children with p=0.001). Conclusion: Age distribution, gender, previous history of febrile seizures and hyponatremia were different between children with and without COVID-19 in SFS. The history of FS was an independent risk factor for non-COVID-19 children with SFS.